Morphometric Variation of Maxilla in Mohammad Hoesin General Hospital - Muzakkie, Mufida; Toline, Lawrencia; Devi, Ratna Sari; Maritska, Ziske (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2024)
Background: Morphometry is a quantitative approach to finding information about variations in the shape of organisms. The maxilla has a central position and plays a vital role in supporting the viscerocranium. Morphometric variations are beneficial in reconstructive procedures and are an essential reference in plastic surgery. However, this study is currently limited. This study aims to determine variations in the maxillary morphometry of patients at Mohammad Hoesin General Hospital that may become a reference for maxillary reconstruction. Method: This descriptive observational study with a cross-sectional approach aims to identify variations in maxillary morphometry in patients treated at RSUP Mohammad Hoesin Palembang. The study is directed at describing a community or society to create an objective picture or description of a condition. It continues by analyzing and comparing maxillary morphometry based on gender. Results: In this study, the results were obtained from as many as 96 samples (male, n = 60, female, n = 36). Variable of male and female were assessed, namely intercanine width (3.58 ± 0.27cm; 3.44 ± 0.18cm), intermolar width (5.64 ± 0.43cm; 5.47 ± 0.27cm), arch length (3.31 ± 0.38cm; 3.32 ± 0.31cm, and palate height (2.46 ± 0.28cm; 2.35 ± 0.22cm) significant results were obtained that the dimensions of the male maxilla were more significant than those of females. Conclusion: There are variations in maxillary morphometry based on gender. Males have larger inter canine width, intermolar width, and palate height morphometry than females.